O-23 Measuring the quality of end of life care: expanding the focus of a standardised death screening tool from why a patient died to how well a patient died. (1st September 2015) - King, Bernadette; Walker, Amanda
Abstract : Background: As part of the introduction of a standardised Admitted Patient Death Screening Tool (APDST) to NSW public health organisations (PHOs) specific criteria relating to end of life (EOL) management were added. Aim: All patients who die in NSW PHOs have their end of l Skorstengaardife management reviewed with regard to comfort and the level of patient and/or family involvement in decision making. Methods: An APDST was developed which includes indicators on the quality of dying. These include whether an existing advance care plan was enacted; the presence of discomfort in the last 48 h of life; the outcome of screening i.e. was death expected or unexpected; and time lapse between decision to palliate and time of death. Results: Since implementation in October 2014, 144 facilities have commenced using the tool with over 3600 (30%) cases screened. Initial results demonstrate that of those patients screened 21% had an advance care plan: 68% had a not for resuscitation order prior to death. Discussion/conclusion: Whilst many clinical departments review deaths to determine if they were preventable or not, or whether a change in condition was detected and acted upon, few review the quality of dying. The introduction of specific measures of the safety and quality of care provided at the EOL provides an opportunity for ongoing monitoring and evaluation of the systems and processes for delivery of this care. This is essential to track performance over time and identify priorities for improvement.